The Genetic Absence Epilepsy Rats from Strasbourg model of absence epilepsy exhibits alterations in fear conditioning and latent inhibition consistent with psychiatric comorbidities in humans. (25th November 2015) - Marks, Wendie N.; Cavanagh, Mary E.; Greba, Quentin; Cain, Stuart M.; Snutch, Terrance P.; Howland, John G.
Abstract: Behavioural, neurological, and genetic similarities exist in epilepsies, their psychiatric comorbidities, and various psychiatric illnesses, suggesting common aetiological factors. Rodent models of epilepsy are used to characterize the comorbid symptoms apparent in epilepsy and their neurobiological mechanisms. The present study was designed to assess Pavlovian fear conditioning and latent inhibition in a polygenetic rat model of absence epilepsy, i.e. Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and the non‐epileptic control (NEC) strain. Electrophysiological recordings confirmed the presence of spike‐wave discharges in young adult GAERS but not NEC rats. A series of behavioural tests designed to assess anxiety‐like behaviour (elevated plus maze, open field, acoustic startle response) and cognition (Pavlovian conditioning and latent inhibition) was subsequently conducted on male and female offspring. Results showed that GAERS exhibited significantly higher anxiety‐like behaviour, a characteristic reported previously. In addition, using two protocols that differed in shock intensity, we found that both sexes of GAERS displayed exaggerated cued and contextual Pavlovian fear conditioning and impaired fear extinction. Fear reinstatement to the conditioned stimuli following unsignalled footshocks did not differ between the strains. Male GAERS also showed impaired latent inhibition in a paradigm using Pavlovian fear conditioning, suggesting that they may have altered attention, particularly related to previously irrelevant stimuli in the environment. Neither the female GAERS nor NEC rats showed evidence of latent inhibition in our paradigm. Together, the results suggest that GAERS may be a particularly useful model for assessing therapeutics designed to improve the emotional and cognitive disturbances associated with absence epilepsy. Abstract : Given the comorbidities in cognition associated with absence epilepsy, we assessed learning and memory in a rat model of absence seizures and its control strain. GAERS demonstrated exaggerated cued Pavlovian fear conditioning and impaired extinction consistent with enhanced anxiety‐like behaviour (Panel A). Male GAERS also showed impaired latent inhibition suggesting their processing of previously irrelevant stimuli in the environment may be altered (Panel B).